Stafne’s bone cavity in a venezuelan population. Prevalence study - Visicchio Cusati, Sabrina (2023)
Objective: To determine the prevalence of the Stafne´s bone cavity in a Venezuelan population and to characterize it radiographically. Method: Descriptive and cross-sectional study. Of 500 panoramic radiographs, those that had radiolucent images in the mandible, circumscribed and not associated with any dental organ, as well as those that could correspond to the mandibular fossa, were selected. Results were collated and discrepancies resolved by consensus. The selected ones were characterized radiographically. The variables were compared using the student's t test for equality of means, applying the Levene test, values of p <0.05 were considered statistically significant. Results: Of the 500 radiographs evaluated, 22 presented images corresponding to deep mandibular fossa or Stafne bone cavities, which represented 4.4%. Of which 5 presented bilaterally (22.7%) and 17 (77, 3%) unilocularly. Among the radiographic characteristics studied, images located in the posterior area (81.81%), without sclerosis (54.54%), continuous to the basal mandibular area, round shape (59.09%) and partial radiolucency (72%) were presented with a higher prevalence). They were more common in male patients with 63.63%. Conclusions: Our results show a higher prevalence of Stafne's bone cavity in a Venezuelan population than that reported in other studies in other populations.